Encryption Symmetric secret Key in Wireless Sensor Network Using AES Algorithm - Hussein, Sahar Najah; Obaid, Ali Hamzah; Jabbar, Ali (Iraqi Journal of Science, 2022)
Wireless sensor network (WSN) security is an important component for protecting data from an attacker. For improving security, cryptography technologies are divided into two kinds: symmetric and asymmetric. Therefore, the implementation of protocols for generating a secret key takes a long time in comparison to the sensor’s limitations, which decrease network throughput because they are based on an asymmetric method. The asymmetric algorithms are complex and decrease network throughput. In this paper, an encryption symmetric secret key in wireless sensor networks (WSN) is proposed. In this work, 24 experiments are proposed, which are encryption using the AES algorithm in the cases of 1 key, 10 keys, 25 keys, and 50 keys. In each experiment, two chains are combined by using a hash function (SHA-2) to produce secret keys. The Network Simulator Version 2 (NS2) was used to assess the network throughput for the generated key. The randomness of the suggested LWM method has been tested by using the Diehard statistical test and the Entropy test. The results of the tests show that the encryption secret keys have a high level of data randomness.